Strategi Peningkatan Mutu Perguruan Tinggi - Muhammad Zamroji (Prodi PAI STIT Raden Santri Gresik, 2020)
If the quality and responsibility of lecturers increases, the education process will become more qualified. If the quality education process is certainly the result of quality education. Quality education by itself will give birth to quality students as well. The strategy to improve the quality and responsibility of lecturers is to try to fulfill the rights of lecturers and create a management climate in the Higher Education Quality Improvement Strategy where he serves to support his career development. It must be underlined that the responsibility of lecturers is not only to educate Student intellectuals but also how to educate students' spiritual lives. A very noble task, but it's not easy.